REQUIRED SAMPLE SIZE FOR EARLY INSTAR LARVAE OF SPRUCE BUDWORM, CHORISTONEURA FUMIFERANA(LEPIDOPTERA: TORTRICIDAE), IN NEWFOUNDLAND - Dobesberger, E. J.; Lim, K. P. (The Canadian Entomologist, 1983)
Abstract Required sample size was determined for early instar (2nd to 4th instar) larvae of spruce budworm, Choristoneura fumiferana (Clem.). Larval counts on mid-crown 45 cm branch tips and whole branches of balsam fir, Abies balsamea (L.) Mill., were described in terms of the negative binomial distribution. The values of common k for the branch tip and whole branch sample units were 1.550 and 1.636, respectively. The required sample size at densities greater than or equal to one appears feasible. It is recommended that the 45 cm branch tip be used to estimate population density of early instar larvae in Newfoundland.